Inflation-Proof Tax System? : Some Lessons From Israel. (IMF Working Papers; Working Paper ;, 1990)
This paper strengthens the claim made by Vito Tanzi that when the effect of a high inflation on the tax system is taken into account, then the overall revenues from inflationary finance may well be negative. The paper analyzes some genuine and neat measures taken in Israel in an attempt to construct an inflation-proof tax system. Despite these very elegant measures, the paper concludes that the Israeli experience suggests that it is more appropriate to talk about the 'inflation subsidy' rather than the 'inflation tax.'.